(untitled) (Jurnal Bahasa Lingua Scientia, 2023)
Lately, technology-enhanced learning tools, such as Nearpod, demonstrate the efficacy of integrating learning, particularly in an English grammar class. This study aims to investigate students’ reactions to technology used for teaching grammar, precisely the acceptance of using Nearpod for grammar class. This study employed a mixed-method design with questionnaire and in-depth interview. The questionnaire used in this study was based on Technology Acceptance Model (TAM) in a Likert scale. Thirty-eight undergraduate students were selected purposefully from Informatics Engineering Department who enrolled in Grammar class. The findings revealed a highly positive perception of Nearpod’s utility for grammar instruction, confirming on students’ acceptance and highlighting its benefits for enhancing language skills, especially in grammar. Students agreed that Nearpod was beneficial to help understand and practice the language. The findings demonstrate that Nearpod is an effective tool for enhancing grammar instruction and suggest its implications for language educators and curriculum designers. This study contributes to our understanding of the role of technology in fostering integrative learning in grammar classes and highlights the need for further research in this area.